"Daddy Pence Come Dance": Queer(ing) Space in the Suburbs. Issue 2 (15th March 2021) - Clark, Jordin
Abstract : Before Mike Pence's inauguration as Vice-President, the LGBTQ activist group Werk for Peace threw a dance protest where over two hundred fiercely fashioned protesters queered Pence's suburban neighborhood. Taking queer as a verb, queering space is a spatial performance, which makes a range of nonnormative enactments, rhythms, movements, and embodiments intelligible by disrupting assumptions that discipline space as binaristic, static, and normative. Outlining three rhetorical performances that queer space, I argue that through dance the Queer Dance Protest queers space by disrupting the heteronormative order, tapping into the space's arena of possibility, and exposing space as open and heterogeneous.